Materiality - Lange-Berndt, Petra; Amato A. , Joseph; Barad, Karen; Butler, Judith; Lange-Berndt, Petra (London : Whitechapel Gallery, 2015)
Adéagbo, Georges ; Andre, Carl ; Antoni, Jantine ; Balkin, Amy ; Barrio, Artur ; Barry, Robert ; Chadwick, Helen ; Chin, Mel ; De Vries, Herman ; Dion, Mark ; Durham, Jimmie ; EXPORT, VALIE; Feyzdjou, Chohreh ; Hazoumè, Romuald ; Kabakov, Ilya ; Kelley, Mike ; Leonard, Zoe ; McCall, Anthony ; Margolles, Teresa ; Morris, Robert ; ORLAN ; Pistoletto, Michelangelo ; Sehgal, Tino ; Shimamoto, Shozo ; Sierra, Santiago : Smithson, Robert ; Starling, Simon ; Thek, Paul ; Vanouse, Paul ; Ukeles, Laderman Mierle ; Walker, Kara.
Formerly CIP.
boek